Discriminative ability of reflex receptive fields to distinguish patients with acute and chronic low back pain - Müller, Monika (2016)
Low back pain has a life time prevalence of 70% to 85%. Approximately 10% to 20% of all patients experience recurrent episodes or develop chronic low back pain. Sociodemographic, clinical, and psychological characteristics explain the transition from acute to chronic low back pain only to a limited extent. Altered central pain processing may be a contributing mechanism. The measurement of reflex receptive fields (RRF) is a novel method to assess altered central pain processing. The RRF area denotes the area of the foot sole from which spinal nociceptive reflexes can be elicited. It was shown to be enlarged in patients with acute and chronic low back pain compared with pain-free individuals. The aim of the study was to explore the discriminative ability of the RRF to distinguish patients with acute and chronic low back pain with the hypothesis that enlarged RRF are associated with chronic low back pain. We included 214 patients with either acute or chronic low back pain and compared RRF between groups in both univariable and multivariable analyses adjusted for different sociodemographic and clinical characteristics possibly associated with the transition to chronic pain. We found a mean difference between patients with acute and chronic low back pain of -0.01 (95% confidence interval [CI], -0.06 to 0.04) in the crude, -0.02 (95% CI, -0.08 to 0.04) in the age and sex adjusted, and -0.02 (95% CI, -0.09 to 0.05) in the fully adjusted model. Our results suggest that the enlargement of RRF area may not be associated with the transition from acute to chronic low back pain.